Looking for An Economically Meaningful Way to Assess Fiscal Policy. (IMF Working Papers; Working Paper, 1989)
This paper examines the behavior of private consumption in Mexico and Chile. Understanding private consumption behavior in developing countries is receiving increasing attention at a time many of them are required to substitute national saving for external saving. For both countries dealt with in this study, changes in the real rate of interest appeared to have a sizable negative effect on private consumption. Private consumption also appeared to be (positively) influenced by real net capital inflows. An empirical approximation to permanent income also appears relevant for both countries, in particular for Mexico, where the sum of the 2-year income elasticities was very close to 1.0. Finally, government consumption did not appear as a relevant variable in either country.